2014
DOI: 10.1038/onc.2014.218
|View full text |Cite
|
Sign up to set email alerts
|

Gα12 gep oncogene deregulation of p53-responsive microRNAs promotes epithelial–mesenchymal transition of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) has a poor prognosis owing to aggressive phenotype. Gα12 gep oncogene product couples to G-protein-coupled receptors, whose ligand levels are frequently increased in tumor microenvironments. Here, we report Gα12 overexpression in human HCC and the resultant induction of zinc-finger E-box-binding homeobox 1 (ZEB1) as mediated by microRNA deregulation. Gα12 expression was higher in HCC than surrounding non-tumorous tissue. Transfection of Huh7 cell with an activated mutant of Gα12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 47 publications
4
53
0
Order By: Relevance
“…Decrease of both miR-192-5p and miR-29a-3p has been shown in HCC cells in several studies [8, 3840], but two other studies have identified these same miRNAs as HCC diagnostic markers increased in the circulation of HCC patients [19, 41]. Our studies are in agreement with the literature on diagnostic circulating miRNA panels which indicate that miR-192-5p and miR-29a-3p have considerable clinical credibility for HCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease of both miR-192-5p and miR-29a-3p has been shown in HCC cells in several studies [8, 3840], but two other studies have identified these same miRNAs as HCC diagnostic markers increased in the circulation of HCC patients [19, 41]. Our studies are in agreement with the literature on diagnostic circulating miRNA panels which indicate that miR-192-5p and miR-29a-3p have considerable clinical credibility for HCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Gna12 KO lowered basal or fasting-inducible SIRT1 expression in skeletal muscle and brown adipose tissue; although the fasting effect on SIRT1 in white adipose tissue seemed to be relatively mild, the inhibitory effect of Gna12 KO on SIRT1 was also observed in this tissue (Supplemental Figure 2). To further evaluate the regulatory role of Gα 12 in lipid metabolism, WT mice were hydrodynamically injected with a plasmid (50 μg) encoding shRNA-Gα 12 (sh-Gα 12 ) or shRNA-nontargeting control luciferase (sh-Luci) via the tail vein for knockdown of Gα 12 in the liver (10). As expected, mice injected with sh-Gα 12 plasmid exhibited diminished SIRT1 and CPT1 expression pared with individuals without steatosis.…”
Section: Gα 12 Ablation Exacerbates Liver Steatosis and Obesity By Sumentioning
confidence: 83%
“…Tae Hyun Kim, 1 Yoon Mee Yang, 1,2 Chang Yeob Han, 1,3 Ja Hyun Koo, 1 Hyunhee Oh, 4 Su Sung Kim,4 Byoung Hoon You, 5 Young Hee Choi, 5 Tae-Sik Park, 6 Chang Ho Lee, 7 Hitoshi Kurose, 8 Mazen Noureddin, 9 Ekihiro Seki, 2 Yu-Jui Yvonne Wan, 10 Cheol Soo Choi, 4,11 and Sang Geon Kim 1 Sirtuin 1 (SIRT1), a NAD + -dependent protein deacetylase, plays a role in the regulation of the transcriptional network in various metabolic processes, especially FA oxidation (14,15). However, the upstream regulator linking cell-surface signaling and SIRT1 is incompletely understood.…”
Section: Gα 12 Ablation Exacerbates Liver Steatosis and Obesity By Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, high E-cadherin and low vimentin expression levels are indicative markers of an epithelial phenotype. A further article by Yang and coworkers contributed to shed light on p53-activated miRNAs contributing to the aggressive mesenchymal phenotype of HCC [30]. Briefly, an overexpression of the oncogenic G protein Gα12 was detected in HCC patients with the resultant induction of ZEB1.…”
Section: Tp53 and Micrornasmentioning
confidence: 99%